CFD analysis onto PU/PIR fitting in rectangular duct - Munisamy K.M.; Yusoff Mohd.Z.; Soon S.P.; Cheong P.W. (2023)
In this study CFD simulation is done on two types of metallic duct design to investigate the pressure drop of flow through an elbow. The PU/PIR duct is new and fast growing integrated material of aluminum and insulation material compacted together to achieve thinner overall thickness as compared to conventional steel ducting with insulation wrapped around it. As compare with sheet metal duct fittings, PU/PIR duct fitting has numerous notches inside the duct fittings. These notches (or grooves) are necessary in the fabrication of fitting components because PU/PIR panel cannot be bent without these notches as the panel is very thick (20mm). On the other hand, sheet metal does not need these notches to be bent since it is thin (0.5-1.2mm). This paper investigates the effect on friction loss of duct fitting with some of these notches in the air stream. A simple 90 degree elbow of 300mmx300mm duct dimension is simulated for comparison. The PU/PIR sheet metal design compared to PU/PIR duct with notch has slight difference in terms of pressure loss. It can be concluded that notches in PU/PIR duct design has negligible effect on the pressure loss but it has numerous advantages compared to conventional HVAC duct fabrication design. The detail results are discussed. 2009 IEEE.